Constructing the fabel: Tony Kushner in conversation with Tom Kuhn - Kuhn, T (Boydell and Brewer, 2018)
The first event of the Recycling Brecht symposium took place on June 25, 2016 (the day after the Brexit vote result was announced) at Oxford’s North Wall Arts Centre, with multi-award-winning playwright Tony Kushner in conversation with Brecht scholar Tom Kuhn.